Initiative and option in transition for doubling farmers’ income - Singh, Manender; Tomar, S. S.; Chaudhary, Gaurav; Tripathi, Siddharth Prakash (Indian Farming, 2018)
The Government of India hasalready planned to take manymeasures to increase farm income,stabilize production and,consequently, improve small farmproductivity. Integrate farmingsystem approach involving synergicblending of crops, horticulture, dairy,fisheries, poultry, etc. seems viableoption to provide regular income andat site employment to small landholder, decreasing cultivation costthrough multiple use of resources andproviding much needed resilience forpredicted climate change scenario.HYV and hybrid seeds are veryessential for a successful cropproduction and increasing the yieldby 15-20% depending upon the cropand it can be further raised up to45% with efficient management ofother inputs. Micro-irrigation alongwith the nutrient application can behighly efficient and priority should begiven to empower farmers withmicro irrigation. The government isaggressively promoting a new cropinsurance (PMFBY) given increasedchallenges by farmers due to frequentclimate disturbances.